Pengaruh Finansial Leverage dan Profitabilitas terhadap Return Saham 6 Bulan Pasca IPO: Studi Pada Perusahaan Yang IPO di Bursa Efek Indonesia Periode 2021-2024 - Hidayati, Surtini Dina; Selvia Eka Aristantia (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to examine the effect of financial leverage and profitability on stock returns six months after an Initial Public Offering (IPO) in companies that went public on the Indonesia Stock Exchange between 2021-2024. Leverage in this study is measured using two variables, namely the Debt-to-Equity Ratio (DER) and the Debt-to-Asset Ratio (DAR), while profitability is measured using Return On Assets (ROA). The sample used in this study consisted of 130 companies that went public between 2021-2024. This study used a quantitative approach with multiple linear regression analysis using SPSS. The results showed that leverage and profitability had a positive but insignificant effect on stock returns six months after the IPO. These findings indicate that investors in the secondary market do not seem to base their investment decisions entirely on financial indicators such as DER, DAR, and ROA in the early period after the IPO. Instead, fluctuations in stock returns six months after the initial listing are more likely to be influenced by external factors, such as market conditions, investor confidence levels, and sentiment towards the company's prospects.